2022
DOI: 10.21037/tcr-21-2686
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and prediction model of ferroptosis related genes in breast cancer

Abstract: Background: The prognosis of patients with breast cancer (BRCA) is difficult to predict because of the high degree of heterogeneity and complex etiological factors. Ferroptosis, an iron-dependent, new form of cell death, plays an important role in regulation of tumor growth and progression. The aim of this study was to clarify the predictive value of ferroptosis-related genes in the overall survival of patients with BRCA. Methods:The messenger RNA expression profile and clinical information of patients with BR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In the ferroptosis program, ROS produced by Fenton reaction damaged the cell membrane and mitochondria, and Fe 3+ prevented GSH from protecting cell membrane and mitochondria [ 41 , 47 , 48 ]. Herein, the Fe 2+ and Mn 2+ in the doping nanostructure triggered Fenton reaction in the presence of H 2 O 2 , then the produced Fe 3+ and Mn 4+ enhanced GSH consumption effect.…”
Section: Resultsmentioning
confidence: 99%
“…In the ferroptosis program, ROS produced by Fenton reaction damaged the cell membrane and mitochondria, and Fe 3+ prevented GSH from protecting cell membrane and mitochondria [ 41 , 47 , 48 ]. Herein, the Fe 2+ and Mn 2+ in the doping nanostructure triggered Fenton reaction in the presence of H 2 O 2 , then the produced Fe 3+ and Mn 4+ enhanced GSH consumption effect.…”
Section: Resultsmentioning
confidence: 99%
“…Research showed that SHARPIN promoted cholangiocarcinoma cell proliferation and inhibited ferroptosis via p53/SLC7A11/ GPX4 signaling [50]. In addition, ferroptosis related elements was identified as potential predictive markers for a variety of cancers, such as liver cancer [51] and breast cancer [52,53]. Immunotherapies are now targeting more than just the CTLA-4 or PD-1 related pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, not all patients derive equal benefits from existing anti-HER2 therapies, and HER2-positive BC is inherently heterogeneous. Although numerous studies have focused on investigating the prognostic significance of ferroptosis-related genes in BC[ 8 - 10 ], analyses specific to BC subtypes are lacking. A more comprehensive understanding of tumor biology and the HER2 signaling pathway is essential for advancing novel strategies to improve patient outcomes.…”
Section: Introductionmentioning
confidence: 99%